IMPLEMENTATION OF GOVERNMENT REGULATION NO. 36 OF 2021 REGARDING REMUNERATION AT PT. GRAND SALMA MANDIRI GRESIK, EAST JAVA - Ruminingsih, Ruminingsih (Universitas Muhammadiyah Sumatera Barat, 2023)
Policy on remuneration for workers is a very crucial and sensitive condition if it doesn't get proper attention from employers. This study aims to examine the implementation of Government Regulation No. 36 of 2021 concerning Remuneration at PT Grand Salma Mandiri Gresik, East Java. In conducting the study, the statutory approach and the empirical approach were used. The results of the study on the implementation of Government Regulation No. 36 of 2021 concerning remuneration, it was found that the company had not complied with these government regulations, in terms of giving remuneration to its workforce, both workers bound by monthly work contract agreements and casual daily work contracts. In the event that Government Regulation No. 36 of 2021 concerning remuneration, administrative sanctions may be given in the form of written warnings, restrictions on business activities, cessation of part or all of the means of production and freezing of business activities.